Analysis of Credit Restructuring Implementation As A Strategy For Handling Problem Credits At PT. BPR Christa Jaya Perdana In Kupang City - Stevi Lodo; Maria I. Hewe Tiwu; Muhammad A. Habibi Mushlih (CV. Vocezmi Learnov, 2026)
This study aims to analyze the implementation of credit restructuring as a strategy for handling non-performing loans at PT. BPR Christa Jaya Perdana, Kupang City, during the 2020–2024 period. This research employs a qualitative descriptive approach, with data collected through in-depth interviews, observation, and documentation involving management and staff directly responsible for credit restructuring. The results indicate that credit restructuring implemented through rescheduling, reconditioning, and restructuring mechanisms is effective in reducing the Non-Performing Loan (NPL) ratio and improving debtors’ repayment capacity, particularly among micro, small, and medium enterprise borrowers. Theoretically, this study reinforces credit risk management theory and agency theory, which emphasize contract adjustment as a key instrument to mitigate default risk and reduce agency conflicts between creditors and debtors. The originality of this study lies in its empirical examination of credit restructuring practices in rural banks as regional financial institutions supporting local economic development. Practically, the findings highlight the importance of strengthening credit analysis, post-restructuring monitoring, and improving debtors’ financial literacy. From a policy perspective, this study provides insights for rural banks and regulators in formulating adaptive and sustainable credit restructuring policies. This study is limited to a single rural bank, thus the findings cannot be broadly generalized.